A retrospective study comparing post-aural versus endaural approach for myringoplasty in cases of chronic otitis media - Nayyar, Supreet Singh; Kaur, Pawandeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Patients diagnosed with chronic otitis media mucosal disease with a mild degree of conductive hearing loss require myringoplasty as their treatment. Various approaches to myringoplasty are defined. The aim of the present study was to compare outcomes of the post-aural versus end aural approach for myringoplasty. Methods: A retrospective cohort study of 26 patients operated over a period of one year at tertiary otorhinolaryngology center. Results: Distribution of approaches among post-aural and end aural was 11 and 15 patients respectively. Otorrhea was the presenting complaint in 65% (n=17) of patients. Preoperative mean pure-tone average (PTA) of all patients was 34.8 dBHL (range 28 to 40 dBHL) while postoperatively 3 months mean PTA was 21.63 and 25.13 dBHL for patients undergoing end aural and post-aural approaches respectively (p=0.008). The success rate in terms of no re-perforation was 76.9% overall, 81.81% for the end aural approach and 73.33% for the post-aural approach with no statistically significant difference (p=0.612). Disease-free survival, as calculated with Kaplan-Meier analysis, was 9.7 and 13.9 months respectively (p=0.807). Cosmetic outcome was analyzed using the scar cosmesis assessment and rating (SCAR) scale. Mean SCAR scale score in our series was 5.36 and 6.20 for patients with end aural and post-aural approaches respectively with no statistically significant difference. Conclusions: Both approaches, end aural and post-aural, are good approaches for the purpose of myringoplasty with no statistically significant difference between the two in terms of re-perforation rates or cosmetic outcomes. However, based on our study, the end aural approach has better hearing outcomes in terms of hearing improvement.